2006
DOI: 10.1177/1074248406290678
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Oral Dronedarone on the Circadian Variation of RR and QT Intervals in Healthy Subjects: Implications for Antiarrhythmic Actions

Abstract: Dronedarone, a non-iodinated benzofuran derivative, was developed as a potentially less toxic alternative to amiodarone. This study describes Holter data of dronedarone in humans. Five groups of healthy subjects were given 1 of 5 oral doses of dronedarone in a twice-daily regimen or placebo. Holter recordings of circadian rhythmicity of RR and QT intervals were evaluated. Dronedarone prolonged RR and QT intervals as a function of dose, without effect on circadian patterns. The relative prolongation of QT, QTc,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…During clinical administration of 400 mg bid, the maximum plasma values of dronedarone range from 84 to 147 ng/ml (approximately 151 to 264 nM), which exceed the WT IhERG IC50 of 42.6 nM in the present study [35]. Dronedarone has been reported to produce concentrationdependent QT interval prolongation in healthy volunteers and cases of excessive QTc prolongation, ventricular ectopy and Torsades de Pointes have been reported in patients receiving dronedarone [36][37][38]. In a recent preclinical study of dogs receiving dronedarone, the drug was found to prolong the Tpeak-Tend interval in a dose-related fashion, suggestive of a propensity to prolong transmural dispersion of repolarization and likely to result from IKr inhibition [39].…”
Section: Relevance Of Potency Of Dronedarone Inhibition Of Ihergcontrasting
confidence: 40%
“…During clinical administration of 400 mg bid, the maximum plasma values of dronedarone range from 84 to 147 ng/ml (approximately 151 to 264 nM), which exceed the WT IhERG IC50 of 42.6 nM in the present study [35]. Dronedarone has been reported to produce concentrationdependent QT interval prolongation in healthy volunteers and cases of excessive QTc prolongation, ventricular ectopy and Torsades de Pointes have been reported in patients receiving dronedarone [36][37][38]. In a recent preclinical study of dogs receiving dronedarone, the drug was found to prolong the Tpeak-Tend interval in a dose-related fashion, suggestive of a propensity to prolong transmural dispersion of repolarization and likely to result from IKr inhibition [39].…”
Section: Relevance Of Potency Of Dronedarone Inhibition Of Ihergcontrasting
confidence: 40%
“…; Wadhani et al. ). Dronedarone has obtained a marketing authorization valid throughout the European Union and the United states granted by the European Commission and Food and Drug Administration in 2009.…”
Section: Introductionmentioning
confidence: 98%
“…; Wadhani et al. ) and with the 400‐mg twice daily dose typically used in clinical trials, the PR interval increased by 13.4 msec, and the incidence of any QTc interval >500 msec was 7.7% (Touboul et al. ; Wadhani et al.…”
Section: Introductionmentioning
confidence: 99%
“…Dronedarone and amiodarone are both considered multichannel blockers, as they inhibit fast sodium channels, possess beta adrenergic blocking effects, and inhibit calcium channels [6,7]. Dronedarone can prolong the action potential duration as well as RR, QT, and QTc intervals [6,10]. Unlike amiodarone, dronedarone has no effect on the Na + /K + pump [7].…”
Section: Chemistry Antiarrhythmic Effects and Pharmacokineticsmentioning
confidence: 98%